2017
DOI: 10.1073/pnas.1700919114
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for ligand binding to an enzyme by a conformational selection pathway

Abstract: Proteins can bind target molecules through either induced fit or conformational selection pathways. In the conformational selection model, a protein samples a scarcely populated high-energy state that resembles a target-bound conformation. In enzymatic catalysis, such high-energy states have been identified as crucial entities for activity and the dynamic interconversion between ground states and high-energy states can constitute the ratelimiting step for catalytic turnover. The transient nature of these state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 49 publications
(58 reference statements)
6
57
2
Order By: Relevance
“…5C). This reduction in activity is consistent with the slowing of the opening and closing of the catalytic site due to the formation of bonds between lid and AMP bd , similar to the effect observed by Kovermann et al [32] by adding a disulphide bond.…”
Section: Computational Arginine Scan Identifies Distinct Mutations Ansupporting
confidence: 89%
See 1 more Smart Citation
“…5C). This reduction in activity is consistent with the slowing of the opening and closing of the catalytic site due to the formation of bonds between lid and AMP bd , similar to the effect observed by Kovermann et al [32] by adding a disulphide bond.…”
Section: Computational Arginine Scan Identifies Distinct Mutations Ansupporting
confidence: 89%
“…However, there is no justification that changes in the equilibrium constant can necessarily lead to an equally measureable effect on catalysis. Whilst our results agree with Kovermann et al [32] who found that an arrested closed conformation reduced catalytic activity, we can't fully conclude that there is a causal relationship. Aviram et al [33] have shown that there is a relationship between the domain opening and closing times that can measurably modulate enzymatic activity, however, this doesn't extend to the open and closed equilibrium.…”
Section: Computational Arginine Scan Identifies Distinct Mutations Ansupporting
confidence: 53%
“…Otherwise, apo-ADK is primarily open. This distribution of free energyimplies that induced fit (and not conformational selection) is at work to enable AP 5 A binding to ADK, a result that matches kinetic assays and NMR results 91,92.…”
supporting
confidence: 68%
“…While the Δ E ZPE and Δ E d–a energies provide insight to the favorability of XB interactions with PCBs, many proteins require ligands to bind in a certain conformation for substrate recognition . For example, different TH orientations were found within the active site(s) of TH‐binding proteins from crystallographic data obtained from the Protein Data Bank .…”
Section: Resultsmentioning
confidence: 99%